Deformability Behavior of St3 Steel Used in the Profiles of High-Voltage Poles - Jutas, A.; Mockiene, J.; Vaiciukynas, V.; Zaldarys, G.; Cinelis, G. (Проблемы прочности, 2018)
The reasons for the difference in mechanical properties of cold-rolled angles made of low-carbon St3 steel used in old designs of high-voltage poles are established. Several kinetic curves for mechanical properties were investigated in terms of tangential and plastic moduli as the most appropriate tool since the integrating parameters can present some strength and deformability differences much more clear at any stage of deformation. The original quantitative characteristics were presented to eliminate the manufacturing quality effect of pole elements and demonstrate the importance of deformation behavior in explaining the microstructural variety. The microstructural phenomena may affect stress levels at the points of yielding, ultimate strength, and fracture. Установлено причини зміни механічних властивостей холоднокатаних кутиків із низьколегованої сталі Ст3 для старих конструкцій високовольтних опор. Вивчено ряд кінетичних кривих, що описують механічні властивості, у вигляді дотичних і пластичних модулів як найбільш прийнятних характеристик, оскільки узагальнені параметри можуть чіткіше відобразити зміну міцності і деформованості на будь якому етапі деформування. Представлено вихідні кількісні характеристики з метою виключення впливу якості елементів опор при їх виготовленні, щоб показати значення деформаційної поведінки для пояснення мікроструктурно ї різноманітності. Мікроструктурні характеристики можуть впливати на рівень напружень у точках плинності, границі міцності і руйнування. Установлены причины изменения механических свойств холоднокатаных уголков, изготовленных из низкоуглеродистой стали Ст3, для старых конструкций высоковольтных опор. Изучен ряд кинетических кривых, описывающих механические свойства, в виде касательных и пластических модулей как наиболее приемлемых характеристик, поскольку обобщенные параметры могут более четко отражать изменения прочности и деформируемости на любом этапе деформирования. Представлены исходные количественные характеристики с целью исключения влияния качества элементов опор при их изготовлении, чтобы показать значение деформационного поведения для объяснения микроструктурного разнообразия. Микроструктурные характеристики могут оказывать влияние на уровень напряжений в точках текучести, предела прочности и разрушения.